Hidden in plain sight: two new species of decapod crustaceans (Palaemonidae and Porcellanidae) discovered in the Red Sea on a university campus in Saudi Arabia - Anker, Arthur; Benzoni, Francesca (Zootaxa, 2023)
Two new symbiotic species of decapod crustaceans, a palaemonid shrimp and a porcellanid crab, are described from the same type locality situated on the campus of the King Abdullah University of Science and Technology (KAUST) in Thuwal, on the Red Sea coast of Saudi Arabia. The palaemonid shrimp Palaemonella jamila sp. nov. is described based on one male and one female, whereas the porcellanid crab Enosteoides habibi sp. nov. is described based on three males and two females. Unfortunately, the originally collected and studied specimens were lost shortly after study. However, subsequent recollection of one specimen of P. jamila sp. nov. and one specimen of E. habibi sp. nov. enabled to deposit a holotype of each new species in the collections of the Florida Museum of Natural History, Gainesville, USA. Both species inhabit burrows of goby-associated snapping shrimps, Alpheus spp., in the shallow subtidal areas, at depths less than 1 m. In addition, a single female specimen of Palaemonella aliska Marin, 2008 collected at Al Fahal reef off KAUST represents the first record of the species in the Red Sea and the Indian Ocean, and a considerable range extension of its previously known distribution range. This species may be a close relative of P. jamila sp. nov., to which it is also ecologically similar. The present study highlights the necessity of prospecting the largely neglected and still undersampled shallow subtidal habitats of the Red Sea, and the Indo-West Pacific in general.